2017
DOI: 10.1103/physrevx.7.031003
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting Molecular Relaxation in Deformed Polymers

Abstract: The flow and deformation of macromolecules is ubiquitous in nature and industry, and an understanding of this phenomenon at both macroscopic and microscopic length scales is of fundamental and practical importance. Here, we present the formulation of a general mathematical framework, which could be used to extract, from scattering experiments, the molecular relaxation of deformed polymers. By combining and modestly extending several key conceptual ingredients in the literature, we show how the anisotropic sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
132
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(143 citation statements)
references
References 151 publications
10
132
1
Order By: Relevance
“…Computer simulations have started to shed light on the molecular origin of strain localization contrary to those from the tube model. Moreover, a recent small‐angle neutron scattering (SANS) study found no evidence to support the basic and central assumption of barrier‐free Rouse retraction that was used to construct the tube theory. In other words, no chain retraction was observed in the SANS measurements, implying that the basis of the tube theory lacks experimental support.…”
Section: Recent Activitiesmentioning
confidence: 99%
“…Computer simulations have started to shed light on the molecular origin of strain localization contrary to those from the tube model. Moreover, a recent small‐angle neutron scattering (SANS) study found no evidence to support the basic and central assumption of barrier‐free Rouse retraction that was used to construct the tube theory. In other words, no chain retraction was observed in the SANS measurements, implying that the basis of the tube theory lacks experimental support.…”
Section: Recent Activitiesmentioning
confidence: 99%
“…However, the flow field produced in these experiments is much more complex than analogous bulk rheology measurements and can lead to transient local inhomogeneities [13,[20][21][22][23], which complicate accurate evaluation of rheological properties. The potential for inhomogeneities can become prohibitively large in nonlinear regimes where the physics is the most intriguing and least understood [1,5,18,21,[24][25][26]. These issues further pose a major obstacle to implementing a microrheological analog of large-amplitudeoscillatory-shear (LAOS) measurements that have been proven extremely effective in elucidating the nonlinear response of polymer systems [27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…Since Wi gives a measure of strain, this formula in principle allows one to determine the microscopic deformation by analyzing the anisotropic component of ( ), from either scattering experiments (via Fourier transform) or computer simulation [1][2][3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experimental and computational studies have demonstrated that the microscopic strain in complex fluids undergoing shear flow is generally not only non-affine, but 3 also dependent on the molecular position [14][15][16][17][18][19][20][21][22][23]. In other words, Eq.…”
Section: Introductionmentioning
confidence: 99%